Thermal ablation system using high intensity focused ultrasound (HIFU) and guided by MRI - Iosif, D.; Milonas, N.; Komodromos, M.; Damianou, Christakis A.; Couppis, A.; Vrionides, F.; HadjiSavas, V.; Ioannides, K. (My University, 2009)
In this paper magnetic resonance imaging (MRI) is investigated for monitoring lesions created by high intensity focused ultrasound (HIFU) in kidney, liver and brain in vitro and in vivo. Spherically focused transducers of 4 cm diameter, focusing at 10 cm and operating at 1 and 4 MHz were used. An MRI compatible positioning device was developed in order to scan the HIFU transducer. The MRI compatibility of the system was successfully demonstrated in a clinical high-field MRI scanner. The ability of the positioning device to accurately move the transducer thus creating discrete and overlapping lesions in biological tissue was tested successfully. A simple, cost effective, portable positioning device has been developed which can be used in virtually any clinical MRI scanner since it can be sited on the scanner's table. The propagation of HIFU can use either a lateral or superior-inferior approach. Both T1-w FSE and T2-w FSE imaged successfully lesions in kidney and liver. T1-w FSE and T2-w FSE and FLAIR shows better anatomical details in brain than T1-w FSE, but with T1-w FSE the contrast between lesion and brain is higher for both thermal and bubbly lesion. With this system we were able to create large lesions (by producing overlapping lesions). The length of the lesions in vivo brain was much higher than the length in vitro, proving that the penetration in the in vitro brain is limited by reflection due to trapped bubbles in the blood vessels. © 2009 American Institute of Physics.
Keywords: MRI; Positioning; Robot; Ultrasound